ENTEROCOCCUS ENDOPHTHALMITIS: Clinical Settings, Antimicrobial Susceptibility, and Management Outcomes. Issue 5 (May 2020) - Dave, Vivek Pravin; Pathengay, Avinash; Braimah, Imoro Zeba; Panchal, Bhavik; Sharma, Savitri; Pappuru, Rajeev Reddy; Mathai, Annie; Tyagi, Mudit; Narayanan, Raja; Jalali, Subhadra; Das, Taraprasad
Abstract : Purpose: To report the clinical presentation and management outcome of patients with endophthalmitis caused by Enterococcus species and to report the susceptibility profile of the isolates. Methods: Twenty-nine cases with culture-proven Enterococcus endophthalmitis from January 2005 to May 2018 underwent vitrectomy/vitreous biopsy, intravitreal antibiotic with or without additional procedures. The undiluted vitreous was subjected to microbiologic evaluation. A favorable anatomical outcome was defined as preservation of the globe, absence of hypotony, attached retina, and absence of active inflammation at the last visit. Favorable visual outcome was final visual acuity ≥20/400. Results: There were 24 men (82.8%). Mean age at presentation was 32.89 ± 25.25 years (median 24 years). Inciting event was open globe injury in 18 (62%), endogenous in 5 (17.24%), postcataract surgery in 3 (10.34%), postscleral buckling in 2 (6.89%), and postkeratoplasty in 1 (3.44%). Enterococcus casseliflavus was the commonest species isolated (14/29, 48.27%) followed by E. faecalis (9/29, 31%). Susceptibility to vancomycin was seen in 27/29 isolates (93%). Visual acuity was ⩽20/400 in all eyes at presentation and ≥20/400 in 10/29 cases (34.48%) at final visit. Anatomical success was seen in 18/29 eyes (62%). Corneal involvement was high at 24/29 eyes (82.75%). Conclusion: Enterococcus is not an uncommon organism in the setting of endophthalmitis after open globe injury. Resistance to vancomycin is rare. Multidrug resistance pattern is restricted to E. faecalis . Visual outcome is poor despite early and appropriate therapy due to inherent organism virulence. Abstract : In this communication, we describe the clinical presentations, microbiology, and management outcomes of Enterococci, a relatively uncommon but clinically significant etiology of endophthalmitis.